South Africa’s symbolic hegemony in Africa - Alden, Chris; Schoeman, Maxi (International politics (Hague, Netherlands), 2015)
South Africa’s position on the African continent is widely seen to be one of dominance and leadership. No longer subject to the international opprobrium, post-apartheid South Africa launched a visionary campaign built around the notion of an ‘African Renaissance’ to restructure continental institutions in line with its interests. This state-led effort was complemented by an aggressive commercial expansion by well-financed South African corporations to break into previously inaccessible markets across the continent. This populist depiction of South Africa is largely echoed in the scholarly literature on South African foreign policy towards Africa. But careful analysis of the South African foreign policy experience both in Africa and more broadly, suggests that these images are only partially realised at best and that they ignore a host of structural problems and outcomes. In particular, the case for South African hegemonic dominance over the continent is challenged by its material weakness and uneven record of foreign policy successes. Despite this, Pretoria is continually ‘rewarded’ with leadership positions in international groupings, such as BRICS, G20 and nearly consecutive terms on the UN Security Council. We argue that this constitutes symbolic representivity and poses a continuing set of foreign policy dilemmas for South Africa and an international community as South Africa struggles to fulfil its hegemonic role in Africa.